Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0479
|View full text |Cite
|
Sign up to set email alerts
|

Impact of essential oils on growth and ochratoxin A production by Penicillium verrucosum and Aspergillus ochraceus on a wheat-based substrate.

Abstract: An in vitro initial screen of twenty-four essential oils for inhibition of spore germination and mycelial growth of mycotoxigenic strains of Penicillium verrucosum and Aspergillus ochraceus was made at 25°C and 0.99 water activity (aw). Based on a measurement of clearing zones, six essential oils were found to be effective in inhibiting growth: bay leaf (west Indian), cinnamon leaf, clove bud, clove leaf (cleaned), lemongrass and thyme. Based on those giving clearing zones greater than 5 mm, three were chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The effects of essential oil of clove and its principal components eugenol, on growth and mycotoxin production by some toxigenic fungal genera like Aspergillus spp., Penicillium spp., and Fusarium spp. had been reported previously (Cairns and Magan 2003, Hope et al 2003, Velluti et al 2003, 2004. This component was able to inhibit both growth and/or mycotoxin production (Bluma and Etcheverry 2008).…”
Section: Discussionmentioning
confidence: 73%
“…The effects of essential oil of clove and its principal components eugenol, on growth and mycotoxin production by some toxigenic fungal genera like Aspergillus spp., Penicillium spp., and Fusarium spp. had been reported previously (Cairns and Magan 2003, Hope et al 2003, Velluti et al 2003, 2004. This component was able to inhibit both growth and/or mycotoxin production (Bluma and Etcheverry 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Chemical residue from fumigants are sometimes found in food and could pose a great danger to the consumer. Cairns et al () observed that issues of poor coverage of the grain often lead to growth of spoilage fungi, especially mycotoxigenic molds; these mold may in fact, metabolize applied chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Growth rate stimulation was observed in some cases when Aspergillus section Flavi grew with the lowest concentration of peperina and peppermint essential oils; however, this stimulation did not occur in all aflatoxigenic isolates. The stimulation on growth rate and mycotoxin production by suboptimal concentration of different essential oils was observed by Cairns and Magan (2002) and Hope et al (2002). Under these conditions, active growth is likely to occur and the imposition of stress could result in a survival or defence response by enhanced mycotoxin production .…”
Section: Discussionmentioning
confidence: 96%